PREDICTION OF FLAMMABILITY CHARACTERISTIC OF MULTICOMPONENT MIXTURE OF REFINERY WASTE WATER LADEN USING ENHANCED QSAR MODEL - SHAARAN, SHT NURUL ASIKHIN (2012)
Study offire and explosion is very important mainly in refineries and industries due to several accidents, which have been reported in the past and present. This study investigates the possibility of the occurrence of fire accident occasioned by the vaporization of hydrocarbon components derived from refinery wastewater drainage systems. In this study, liquid sample containing mixtures ofhydrocarbon products and water were collected from a refinery's drainage system that is located near to the naphtha unit. The liquid sample in thp initial stafrp wqg <?nhjprtpd in n dktillntinn process to separate the oil and water contents. Then, the oil-liquid phase was analysed using Gas Chromatography Mass Spectrometry (GC-MS) to examine the compositions of the sample. The results obtained indicate that there are 77 hydrocarbon components ranging from C9 to C22- Mole fractions of components in the liquid phase were obtained from the GC results. Meanwhile, modified Roult's law equation is used to calculate the mole fractions ofthe components in the gas phase as the mixture in this study is considered as a real solution. The activity coefficients were calculated using UNIversal Functional Activity Coefficient (UNIFAC) method; while the fugacity coefficients were obtained by using Peng Robinson method. Lower Flammability Limits (LFLS) and Upper Flammability Limits (UFLS) for individual components were calculated using stoichiometric concentration method. The results were compared with others obtained from DIPPR 801, experimental and developed models. The results show good agreement between the experimenM and calculated values. The LFLmjx and UFLmjx for the mixture were calculated in accordance with Le Chatelier equationJn this study, the LFLmix for the mixture is calculated at 0.74vol% and 4.71vol% for UFLmjx. Meanwhile, the Limiting Oxygen Concentration (LOC) for the mixture is 11.48vol%. Based on these results, a flammability diagram method was used to show the flammability region ofthe vapour mixture and then to examine ifthe vapour mixture is considered a flammable mixture or not. Due to the importance of flammability limits, flash point (FP), autoignition temperature (AIT), and limiting oxygen concentration (LOC) to identify flammability characteristics, a Quantitative Structure Activity Relationship (QSAR) model has been developed to estimate these properties. The results from the developed models were validated with other data obtained from experimental works and published literatures to confirm the accuracy ofthe developed model. Furthermore, the accuracy of the developed model was compared with other QSAR models, which have been developed by other researchers. The results showed that the accuracies of the proposed models are the highest among other available models. Moreover, in this work the effect of boiling point, molecular weight, and vapour pressure on flash point temperature and autoignition temperature were studied and discussed. Results showed that for most of the components as the boiling point, and the molecular weight increasing the flash point temperatures tend to increase. The results obtained were used to propose suitable inherent safer methods to prevent the flammable mixture from occurring and to minimizing the loss of properties, business and life due to fire accidents^